EFFECT OF FOLIAR APPLICATION WITH POTASSIUM SULPHATE AND ASCORBIC ACID ON GROWTH AND FLOWERING OF DAHLIA (Dahlia variabilis L. cv. ARIZONA) - Mohammed, Sarah Ali; Abd-Allatif, Sawsan Abdullah; Obaid, Ayad Assi (Diyala Agricultural Sciences Journal, 2016)
Afield experiment were conducted on Dahlia (Dahlia variabilis L. cv. Arizona) at Fahama/Baghdad Provence during spring at 16March to explain the effect of foliar spray of Potassium Sulphate K2SO4(0, 3.5 and 5gl-1) and Ascorbic acid or Vit.C (0, 50 and 100mgl-1) on vegetative and flowering growth characters. Results showed that spraying of K2SO4 at 5gl-1 and 100mgl-1 of Vit.C lead to increasing of plant high, number of leaves significantly, as well as chlorophyll percent (spad unit) and the percent of mineral elements (NPK) comparing the control treatment, as well as increased the number of inflorescence and elongated the period of inflorescence keeping quality and arrangement ability on plants, while caused delay the first inflorescence appearance(day).